A Critical Discourse Analysis of the Pantene Advertisement - Allikathus Rizky Laily F (ITScience (Information Technology and Science), 2022)
Advertisement is one mass media used to inform, persuade and change people's perspective on the world. This research aims to analyze Pantene advertisement’s textual features, discourse practice, and socio-cultural practice. The method of this research is a qualitative approach. This research uses a critical discourse analysis approach with Fairclough’s three-dimensional model. The data source was taken from videos in Pantene advertisements with the English Version and their translation taken from YouTube. The result of this research is in the textual feature of Pantene Advertisement using a first personal pronoun, additive conjunction, positive adjective, and negative adjective. In the discourse practice, the advertisers create the advertisement to show that they are trying to display the beauty standards that have been circulating in society regarding how the ideal hair should be. And the targets of this Pantene advertisement are teenagers who want to have perfect hair, which is to have long, black, and shiny hair. In the situational level, Pantene advertisement was launched because many people have not maintained hair conditions, and in the institutional, the advertisers present various innovations in their production. This is assumed to have implications for what the community wants. In the social feature, Pantene contributes to the circulation of beauty products, especially in the hair care section. Pantene consistently innovates following developments in society, so many products from Pantene are in demand to beautify the appearance of their hair. Advertisers show their power by advertising the products they make.